Successful pregnancy for primary amenorrhea and recurrent implantation failure and the role of hysteroscopic adhesiolysis: a case report - Khrait, Zakwan (J Med Case Rep, 2019)
BACKGROUND: Infertility continues to be an enigmatic and emerging problem. Although in vitro fertilization has proved to be revolutionary and immensely beneficial to many people, it is far from perfect, and many women experience recurrent in vitro fertilization failures. There can be a multitude of factors involved in recurrent in vitro fertilization failures. The aim of this report was to explore the role of hysteroscopy in determining potential causes of in vitro fertilization failure and how the relevant hysteroscopic findings can address the issue of infertility in terms of a subsequent successful in vitro fertilization. CASE PRESENTATION: A 37-year-old white Arab woman with a history of eight in vitro fertilization failures and one curettage performed for a blighted ovum presented to our hospital because of inability to conceive. Her past medical history was significant for hypothyroidism and positive factor V Leiden. She underwent hystero contrast sonography, which revealed a normal uterine cavity with irregular fillings in the right corner. To explore this further, hysteroscopy was performed, which showed dense adhesions in the right upper corner and first-degree adhesions in the lower half of the uterus. After undergoing adhesiolysis and a cycle of estradiol valerate and progesterone, the patient successfully conceived twins. CONCLUSIONS: Hysteroscopy may play an important role before or in conjunction with assisted reproductive techniques to help infertile women and couples achieve their goals of pregnancy and live birth of a child.